Service Quality and Education Cost Implication the Decision to Stay Active Re-Study Mediated by Student Satisfaction – A Study at Private University in West Java (European Journal of Marketing and Economics, 2023)
This study aims to rigorously analyze the implications of service quality variables and education costs in relation to student satisfaction, as well as their subsequent impact on the decision of students to remain active and re-enroll at private universities in West Java. Employing a comprehensive survey method, the researchers gathered primary data through the distribution of detailed questionnaires to a representative population of private university students within the region. To ensure statistical depth, the data were processed using Structural Equation Modeling (SEM) via AMOS 18, allowing for a sophisticated examination of complex variable interactions. The empirical results conclude that a student's decision to stay active and pursue further study is significantly driven by both service quality and education costs, with student satisfaction acting as a critical mediating variable. Ultimately, the findings suggest that academic institutions must optimize both service delivery and pricing strategies to foster the long-term loyalty and satisfaction of their student body.
Keywords: Quality of Service, Cost of Education, Student Satisfaction, Student Decision